PERALIHAN HAK ATAS TANAH AKIBAT TANAH TERLANTAR (STUDI KASUS TERHADAP KEPUTUSAN KEPALA BADAN PERTANAHAN NASIONAL REPUBLIK INDONESIA NOMOR 10/PTT-HGU/BPN RI/2012) - Eko Yulinggar Permana; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In accordance with Article 2 Paragraph (1) On the basis of BAL that the provisions of Article 33 Paragraph (3) of the Constitution and the matters referred to in Article 1, earth, water and air space, including natural resources contained within the at the highest levels controlled by the State, as the organization of the whole power of the people. Therefore, the soil must be maintained well in order to achieve the goal of BAL. The purpose of writing this thesis, first, criteria and control of land belonging to the wastelands based on Government Regulation No. 11 Year 2010 on the Control of Neglected and Land Utilization, Second, transfer of land rights as a result of abandoned land (Decree of the Head of the National Land Agency Number 10/PTT-HGU/BPNRI/2012)Type of research is Normative legal research, data sources used, the primary data, secondary data, and the data tertiary, data collection techniques in this study with interviews and literature study.From the research, there are two main things that can be concluded. First, that the criteria wastelands under Government Regulation No. 11 Year 2010 on Control and Abandoned Lands Pendayaguaan is the holder of the rights that are not using or use but does not fit with the purpose of granting rights and not the rights forever digunakanya 3 years since the permission granted, Second, transfer of land rights as a result of abandoned land (Decree of the Head of the National land Agency Number 10/PTT-HGU/BPN RI/2012) dengancara invetarisasi, identification, peringatandan enetapan. advice authors, first, it is expected that the National Land Agency to disseminate the rules on the prohibition of land abandonment. Second, it is expected that the National Land Agency to take action against violations of wastelands,